Food, Conservation, and Energy Act of 2008: Farmland Protection Program (FPP) - Hicks, Erin, author; Seidl, Andrew, author; Colorado State University, Department of Agricultural and Resource Economics, publisher (Colorado State University. Libraries, 2008)
Congress established the Farmland Protection Program (FPP) in the 1996 Farm Bill to limit nonagricultural uses of certain agricultural lands. The program was renamed the Farm and Ranch Land Protection Program (FRPP) for the 2002 Farm Bill, and changed back to the FPP in 2008. The objective of the Farmland Protection Program is to help farmers and ranchers keep their working agricultural land in agriculture. Producers voluntarily sell conservation easements for their land in exchange for rental payments. Purchasing organizations for the conservation easements include the USDA itself, state and governmental organizations.
Farmland Protection Program (FPP)
October 2008 Agricultural and resource policy report, no. 7
October 2008.
Keywords: Farmland Protection Program (FPP); Land use, Rural -- Law and legislation -- United States; Land use, Rural -- United States; Incentives in conservation of natural resources -- United States; Rural development -- Law and legislation -- United States; Contracts, Agricultural -- United States; Agricultural conservation -- United States; Natural resources -- Law and legislation -- United States; Agricultural laws and legislation -- United States; Agricultural subsidies -- Law and legislation -- United States